Percepciones Y Caracterización De Pastizales En Los Cantones Joya De Los Sachas Y Francisco De Orellana - Marcillo, Raúl Lorenzo González; Pupo, Juan Rafael Perez (European Scientific Journal, ESJ, 2018)
This paper focuses on determining the perception and characterization of the pastures in the farms of livestock producers and researchers in the Canton Sachas and Francisco Orellana, Province of Orellana, Ecuador. Their objective was to understand the use and management of Amazonian tropical pastures. Seventeen cattle farms of 8 communities were characterized to observe the characterization of the farmers, land use, use of forage banks, pasture management, and bovine cattle housing. A semi-structured interview was designed to collect primary information about the problem under investigation. When characterizing the farmers in relation to land use, before 47.5% of the producers were engaged in agriculture, today 85.9% carry out livestock work with silvopastoral practices. Only 14.1% were dedicated to agriculture and the production of coffee and cocoa. Regarding the use of feed banks, 35.29% have more food for their animals, while 5.88% have better environmental conditions. In addition, 77.6% of the farmers mentioned that they have improved their production with the use of the feed bank. In conclusion, the results indicate that small and medium producers can benefit from silvopastoral systems as an alternative to improve production and not affect the environment.